HUKUM MEWAKAFKAN POLIS ASURANSI - Mubarok, Jaih; Hasanuddin, Hasanuddin (Islamic Economics and Business Faculty of UIN Antasari, 2016)
Abstract: The endowment policy conducted by three domains: 1)insurance knowledge domain; 2) endowment theory domain; and 3) will theory domain. These three domains of this is expected to helpfnd a solution for the ideas and endowment policy movement in Indonesia in terms of sharia. The study of three domains conducted in order to seek the clarity of legal insurance policy endowment in terms of sharia which showed at least two topics, frst, there is a special element in the insurance, namely welfare. Second, the object of endowment must already be affrmed of wakif during the donated / written endowment; and Musha bih (the object ofthe will) must already belong to Mushi (which intestate) at the time the will is affrmed/written orwhen the nafdaz will (effective), that is when Mushiis died.Abstrak: Kajian wakaf polis dilakukan dengan tiga domain: 1) domain ilmu perasuransian; 2) domain teori wakaf; dan 3) domain teori wasiat. Tiga domain kajian ini diharapkan dapat membantu mencari solusi atas ide dan gerakan wakaf polis di Indonesia dari segi syariah. Tiga domain kajian yang dilakukan dalam rangka mencari kejalasan hukum wakaf polis asuransi dari segi syariah memperlihatkan setidaknya dua topik, yaitu Pertama, dalam asuransi terdapat unsur khusus, yaitu kemashlahatan. Kedua, obyek wakaf harus sudah menjadi milik wakif pada saat akad wakaf diikrarkan/ditulis; dan musha bih (obyek wasiat) harus sudah menjadi milik Mushi (yang berwasiat) pada saat akad wasiat diikrarkan/ditulis atau pada saat wasiat nafdaz (efektif), yaitu Mushi meninggal dunia.Kata Kunci: Waqaf, asuransi, wasiat, polis, syariah.